Application of empathy theory in the study of the effectiveness and timeliness of information dissemination in regional public health events - Min Zhang; Xiaobing Lu (Frontiers Media S.A., 2024)
IntroductionThis study examines the role of empathy theory in enhancing the effectiveness and timeliness of information dissemination during regional public health events, with a focus on the SARS and COVID-19 pandemics as case studies. Utilizing an anthropological interview method, the research delves into the public's transformation from passive recipients to active participants in information dissemination, emphasizing the impact of empathy.ObjectiveThe study aims to evaluate the application of empathy theory in the context of public health emergencies and to determine its influence on the quality of information dissemination and public engagement.MethodsThe research involved two distinct surveys, each collecting 50 questionnaires from participants in different regions, to capture a diverse range of perspectives. The surveys assessed participants' views on information dissemination, their levels of empathy, and their behaviors in receiving and sharing health-related information.ResultsThe findings indicate that empathy plays a crucial role in facilitating the active involvement of the public in information dissemination. There is a notable difference in the public's emotional response and information sharing behaviors between regions with direct experience of the health events and those less affected.ConclusionThe study concludes that empathy theory, when applied to information dissemination during public health emergencies, can significantly improve the public's engagement and the overall effectiveness of communication strategies. The results underscore the need for empathetic communication to foster a sense of solidarity and collective action in response to public health crises.